Assessment of Antioxidant Activity of Crude and Purified Bio-active Compound, Embelin in Aegiceras corniculatum (L.) Blanco: A Less-explored Mangrove Plant - Mohapatra, Manisha; Basak, Uday Chand (Indian Journal of Pharmaceutical Education and Research, 2021)
Context: Most of the Mangrove species are vital basically in terms of economic, environmental and medicinal point of view as several Mangrove species are used for preparation of many drug formulations. In this aspect, Aegiceras corniculatum is a unique black Mangrove plant. Aim: In this study antioxidant potency of different parts of A. corniculatum was evaluated through measuring the antioxidant parameters along with a comparative assessment between the crude extracts and the purified embelin isolates. Settings and Design: For this purpose, two different extraction procedures were opted along with two different solvent systems to confirm the viability of antioxidant values obtained from different plant parts of Aegiceras corniculatum. Methods and Materials: Antioxidant parameters like Phenol, Flavonoid, Total antioxidant content, 2, 2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), Reducing power were quantified from all the extracted plant part samples. Statistical analysis used: The results of the non-enzymatic parameters of antioxidant activity of both the crude plant extracts and the purified embelin samples were analysed through Two Way Repetitive Measure ANOVA using GRAPHPAD PRISM software version 6.05. Results: From the results, crude extracts along with isolated compounds had shown better antioxidant potency particularly in fruit followed by root, stem bark and leaf. Optimization of extraction process validated Soxhlet method to be a superior one. Conclusion: Crude extracts were found to be superior to purified isolates in terms of antioxidant potency. All samples showed remarkable antioxidant potency hence can be used in medicinal industries.
Keywords: Aegiceras corniculatum; Antioxidant; DPPH; FRAP; Reducing Power